A Comparative Study Of Serum Magnesium In Pulmonary Tuberculosis And Bronchial Asthma - BISWAJIT DAS; PRASANNA CHANDRA; K.V. THIMMARAJU (International Journal of Pharma and Bio Sciences, 2011)
This study was undertaken in 120 subjects, 40 diagnostic cases of pulmonary tuberculosis (group I), 40 diagnostic cases of bronchial asthma (group II), and 40 normal control groups (group III). Magnesium levels were analyzed from serum by spectrophotometer, using calmagite method. Our study shows a significant decrease (<.0001) serum magnesium levels in group I (pulmonary tuberculosis) and group II (bronchial asthma) cases as compared to group III (Control). Our study also reveals that the mean levels of serum magnesium are markedly lower in cases having far advanced disease (1.25±.080 meq/L) than in those with moderately advanced disease (1.37±.084 meq/L) or with minimal disease (1.50 meq/L).